Monitoring fiscal adjustments in the European Union and EMU - Rolf Strauch (Deutsche Bundesbank, 1999)
The international monitoring of public finances in EMU member states is an essential element of the Stability and Growth Pact. Part of evaluating government budgets involves determining the sustainability of the envisaged consolidation measures. The academic and political debate on this topic emphasises various criteria which suggest persistent consolidation efforts. The academic literature stresses the contribution which government consumption and transfer payments make to reducing the deficit. The literature . also indicates a significant reversal in previous trends which had been responsible for expanding the deficit. In its Convergence Report of 1998 and in background studies, the European Commission cited the reduction of primary expenditure as a criterion of sustainability. Although various criteria have been mentioned in the debate, it is important to note that the empirical support for these criteria is based largely on the same data and methods, which are subject to certain shortcomings ... – – Die internationale Überwachung der Entwicklung öffentlicher Finanzen in den Mitgliedstaaten der EWWU ist wesentlicher Bestandteil des Stabilitäts-und Wachstumspaktes. Teil der Bewertung der Staatshaushalte ist es, die Dauerhaftigkeit der angestrebten Konsolidierungsmaßnabmen zu beurteilen. Die wissenschaftliche und politische Diskussion zu diesem Thema betont verschiedene Kriterien, die auf anhaltende Konsolidierungsbemübungen hinweisen. In der wissenschaftlichen Literatur wird zum einen der Beitrag des Regierungskonsums und der Transferleistungen zur Verringerung des Defizits hervorgehoben. Darüber hinaus verweist die Literatur darauf, daß die Umkehrung vorheriger Trends, die für die Ausweitung des Defizits verantwortlich waren, von Bedeutung ist. Die Europäische Kommission hat in ihrem Konvergenzbericht von 1998 und in Hintergrundstudien die Reduzierung der primären Ausgaben als Nachhaltigkeitskriterium genannt. Obwohl verschiedene Kriterien in der Diskussion genannt werden, ist festzustellen, daß die empirische Fundierung dieser Kriterien weitgehend auf denselben Daten und Methoden beruhen, mit denen sich aber gewisse Nachteile verbinden ...
Keywords: 330